A case of Degos disease in pregnancy. (December 2016) - Sharma, Sapna; Brennan, Barbara; Naden, Ray; Whelan, Patrick
Degos disease is characterized as a rare systemic vaso-occlusive disorder, although the exact pathophysiology is uncertain. Fewer than 200 patients have been reported in the literature, and only two reports describe the course of the disease during pregnancy. Here, we present the first reported case of the course of pregnancy in a woman with the systemic form of Degos disease. The patient had been diagnosed with Degos prior to pregnancy and was monitored throughout the duration of the pregnancy. Her presentation and treatment are described. There was no further exacerbation secondary to the pregnancy itself; the pregnancy course was uncomplicated and the baby unaffected to date.